“Sin of the Fathers upon the children to the third and fourth generation” : an appraisal of Exodus 20:5 and Deuteronomy 5:9 in relation to an African Theological understanding of original sin - Takore, Zachariah Bulus (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.